2013
DOI: 10.4012/dmj.2012-312
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed hardness testing system, “Cariotester”: Measurement principles and development of a program for measuring Knoop hardness of carious dentin

Abstract: We previously discovered that when a cone-shaped indenter coated with paint was pressed into an object, the paint disappeared in accordance with the depth of the indentation. Based on this fact, we developed the Cariotester, a portable system for measuring the Knoop hardness (KHN) of carious dentin. The Cariotester is composed of a handpiece with an indenter, a microscope, and a computer. In this system, the painted indenter is forced into the material with a 150-gf load, and the indentation depth (CT depth) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Recently, a newly developed hardness system to measure Knoop hardness has been introduced with the advantage that it is simple, quick and can be used to measure an unpolished surface 26) . In this study, this device was used to measure KHN of non-eroded and eroded surfaces of cut and uncut enamel samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a newly developed hardness system to measure Knoop hardness has been introduced with the advantage that it is simple, quick and can be used to measure an unpolished surface 26) . In this study, this device was used to measure KHN of non-eroded and eroded surfaces of cut and uncut enamel samples.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, both of these methods have precluded the use of a microhardness tester to measure white spot surface hardness. The Cariotester, on the other hand, uses a novel method in which the indentation depth is determined by measuring the width of lost paint from the indenter 4) , thus enabling measurement of hardness on the outermost surface of the white spot.…”
Section: Discussionmentioning
confidence: 99%
“…The hardness is calculated from the depth to which the indenter presses into the tooth surface. It also has the other advantages that one measurement only takes around 10 s to perform 12) , it can be used to measure hardness on non-flat tooth surfaces, and can be used intra-orally. The Cariotester is the world's first hardness tester that can be used at the chairside 12) .…”
Section: Introductionmentioning
confidence: 99%
“…It also has the other advantages that one measurement only takes around 10 s to perform 12) , it can be used to measure hardness on non-flat tooth surfaces, and can be used intra-orally. The Cariotester is the world's first hardness tester that can be used at the chairside 12) . Featherstone et al reported that there is a linear relationship between the square root of the Knoop hardness of demineralized dentin and mineral density measured by transverse microradiography (TMR), which is regarded as the gold standard [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation